2007
DOI: 10.1074/jbc.m704326200
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Loop at the Active Center of the Escherichia coli Pyruvate Dehydrogenase Complex E1 Component Modulates Substrate Utilization and Chemical Communication with the E2 Component

Abstract: Our crystallographic studies have shown that two active center loops (an inner loop formed by residues 401-413 and outer loop formed by residues 541-557) of the E1 component of the Escherichia coli pyruvate dehydrogenase complex become organized only on binding a substrate analog that is capable of forming a stable thiamin diphosphate-bound covalent intermediate. We showed that residue His-407 on the inner loop has a key role in the mechanism, especially in the reductive acetylation of the E. coli dihydrolipoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 33 publications
9
60
0
Order By: Relevance
“…5B and ref. 4) and crystal structure (3,4)], the K d PLThDP significantly increased, whereas the rate of PLThDP formation (in E401K) significantly decreased. This suggests that preequilibrium may ''be harvested for catalytic turnover'' (25).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5B and ref. 4) and crystal structure (3,4)], the K d PLThDP significantly increased, whereas the rate of PLThDP formation (in E401K) significantly decreased. This suggests that preequilibrium may ''be harvested for catalytic turnover'' (25).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that on E1ec, it is difficult to observe the AP form. However, addition of pyruvate to the E401K loop variant under a variety of conditions produced the negative CD band corresponding to MC, stabilized as a result of very slow catalysis caused by impaired loop dynamics (4). It could be shown that the MC is fully formed in E1ec and E401K, as measured with SF-CD, within the dead time of the instrument (1 ms) (SI Fig.…”
Section: Loop Dynamics Influences Covalent Addition Of the Substrate mentioning
confidence: 94%
See 3 more Smart Citations